2001
DOI: 10.1074/jbc.m103574200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Interleukin-18 in Adhesion Molecule Induction through NFκB and Phosphatidylinositol (PI) 3-Kinase-dependent Signal Transduction Pathways

Abstract: Interleukin-18 (IL-18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 41 publications
9
114
1
Order By: Relevance
“…In fact, it was demonstrated that culture supernatants from DENV infected primary human monocytes could activate endothelial cells by eliciting expression of VCAM-1 and ICAM-1 in these cells (Anderson et al 1997). Interestingly, the IL-18 plasma levels were positively correlated with sICAM-1 levels together with the expression of CD54 on T CD8 cells, as described previously that IL-18 increases the expression of ICAM-1 (Morel et al 2001) and VCAM-1 (Vidal- Vanaclocha et al 2000), enhancing the recruitment of lymphocytes into inflammatory tissues. Furthermore, our study revealed that CD8 + T cells expressing HLA-DR were significantly present in higher frequency in Severe Dengue cases.…”
Section: Table IIImentioning
confidence: 61%
See 1 more Smart Citation
“…In fact, it was demonstrated that culture supernatants from DENV infected primary human monocytes could activate endothelial cells by eliciting expression of VCAM-1 and ICAM-1 in these cells (Anderson et al 1997). Interestingly, the IL-18 plasma levels were positively correlated with sICAM-1 levels together with the expression of CD54 on T CD8 cells, as described previously that IL-18 increases the expression of ICAM-1 (Morel et al 2001) and VCAM-1 (Vidal- Vanaclocha et al 2000), enhancing the recruitment of lymphocytes into inflammatory tissues. Furthermore, our study revealed that CD8 + T cells expressing HLA-DR were significantly present in higher frequency in Severe Dengue cases.…”
Section: Table IIImentioning
confidence: 61%
“…In addition, levels of IL-18 have been directly correlated with soluble ICAM-1 in plasma and also with CD8 T cells expressing ICAM-1 (Table III). In fact, previous data demonstrated that IL-18 increases the expression of adhesion molecules ICAM-1 and VCAM-1 (Morel et al 2001), which facilitate the emigration of neutrophils and lymphocytes in containing a nidus of infection, thereby contributing to the primary process in inflammatory diseases.…”
Section: Correlation Between Il-18 With Soluble and Surface Icam And mentioning
confidence: 99%
“…Quiescent cardiomyocytes were treated with IL-18 for 1 h. Cytoplasmic and nuclear protein extracts were analyzed for GSK3␤ levels by Western blotting. (32). Therefore, we analyzed PI3K activation following IL-18 treatment by PI3K lipid kinase assays.…”
Section: Il-18 Induces Cardiomyocyte Hypertrophy-il-18 Signals Via Ilmentioning
confidence: 99%
“…A possible explanation for the reduced recruitment of ␣␤ T cells to the target tissue could be an altered expression of adhesion molecules due to the functional inactivation of IL-18 during CHS. As reported earlier, IL-18 enhances the expression of VCAM-1, ICAM-1, and E-selectin on endothelial cells (37). The up-regulation of VCAM-1 on hepatic sinusoidal endothelium by IL-18 has been implicated in hepatic melanoma metastasis (38).…”
Section: Discussionmentioning
confidence: 64%